Signaling Models for the Valuation of IPOs: An Empirical Test of IPOs in China (1993-2004) - He, Xiaofan (2006)
This dissertation empirically tests the IPO signaling models including Leland & Pyle (1977) capital structure model, Bhattacharya (1979) & Heinkel (1978) dividend model, Krinsky & Rotenberg (1989) firm risk model and a new multivariable model based on the Chinese IPO issuing market data. The regression result not only support the above existing literatures, and also prove that other factors such as state-owned or not according to the special market features in China, plays an important role in the valuation of IPOs as well. Moreover, it can be concluded from the results that the better the information disclosed, the more rational the IPO price will be.